Effects of Fenugreek Seeds on the Severity and Duration of Pain in Primary Dysmenorrhea in the Students at Hamadan University of Medical Sciences, Iran (2016) - Seyedeh Zahra Masoumi; Arezoo Shayan; Hassan Ahmadinia; Reyhaneh Ebrahimi; Roya Ahmadi Niyatabesh; Shirin Moradkhani; Maryam Farhadian; Farzaneh Soltani (Mashhad University of Medical Sciences, 2018)
Introduction: Dysmenorrhea is a common disorder that manifests during the menstrual cycle, causing cramps in the lower abdomen. The discomfort interferes in the daily activities of the individual. The present study aimed to evaluate the effects of fenugreek seeds on the severity and duration of pain in primary dysmenorrhea in the students at Hamadan University of Medical Sciences, Iran. Methods: This randomized, controlled clinical trial was conducted on 100 students at Hamadan University of Medical Sciences in 2016. The subjects were equally divided into two groups of intervention (Fenugreek seeds) and control (placebo). Medications were administered for two months. Data were collected using demographic questionnaires, McGill pain questionnaire, and multidimensional speech scale before the intervention and one and two months after the medication administration. Data analysis was performed in SPSS version 19 using independent and paired t-test and Chi-square at the significance level of <0.05. Results: In the group receiving Fenugreek seeds, mean duration and severity of primary dysmenorrhea pain decreased significantly at the end of the first and second cycle of the intervention (P<0.01). Moreover, mean number of the analgesics used in the intervention group significantly reduced compared to the control group at the end of the first and second cycle of the intervention, while the mean number of menstruating days increased with a significant difference (P<0.01). Conclusion: Considering the positive impact of fenugreek seeds on reducing the severity and duration of the symptoms of primary dysmenorrhea with fewer side-effects than chemical drugs, it is recommended that this herbal compound be used in the treatment of this disorder.